Characterization of implementation limits and identification of optimization strategies for sustainable water resource recovery through life cycle impact analysis. (December 2019) - Pan, Yi-Rong; Wang, Xu; Ren, Zhiyong Jason; Hu, Chengzhi; Liu, Junxin; Butler, David
Graphical abstract: Highlights: Life cycle impacts of water reclamation for crop irrigation were investigated. The net gains of reclaimed water were dependent on the sophistication of processes. The benefits of water resource recovery can be offset by other unwanted effects. Expanded simulations were performed to explore potential solutions. Integration of resource recovery and green approaches was identified as a solution. Abstract: How we manage alternative freshwater resources to close the gap between water supply and demand is pivotal to the future of the environment and human well-being. Increased scarcity of water for agricultural irrigation in semi-arid and arid regions has resulted in a growing interest in water reuse practices. However, insight into the life cycle impacts and potential trade-offs of these emerging practices are still limited by the paucity of systematic evaluations of different water reuse implementations. In this study, a host of environmental and human health impacts at three implementation levels of allowing water reclamation for crop irrigation was comparatively evaluated across the operational landscape via a combination of scenario modelling, life-cycle impact analyses and Monte Carlo simulations. Net harvesting of reclaimed water for irrigation was found to be dependent upon the sophistication of the treatment processes, since multistage and complex configurations can cause greater direct water consumption during processing. Further, the direct benefits of water resource recovery can be essentially offset by indirect adverse impacts, such as mineral depletion, global warming, ozone depletion, ecotoxicity, and human health risks, which are associated with increased usage of energy and chemicals for rigorous removal of contaminants, such as heavy metals and contaminants of emerging concern. Nonetheless, expanded simulations suggest the significance of concurrently implementing energy recovery, nutrient recycling, and/or nature-based, chemical-free water technologies to reduce the magnitude of negative impacts from engineered water reclamation processes.